Purification, characterization and mechanism of action of enterocin HDX-2, a novel class IIa bacteriocin produced by Enterococcus faecium HDX-2. (January 2022) - Du, Renpeng; Ping, Wenxiang; Ge, Jingping
Abstract: A novel bacteriocin was isolated and purified by salt precipitation, C8 cartridge extraction, cation exchange and RP-HPLC. SDS-PAGE and MALDI-TOF-MS analysis showed that the Ms of enterocin HDX-2 5482 Da. The enterocin HDX-2 was sensitive to protease degradation; was stable in large pH range (pH 2–10); was heat stable (121 °C, 20 min); was stable in organic solvents, surfactants, and detergents; metal ion balance and bactericidal activity toward foodborne spoilage-associated and pathogenic bacteria. This novel enterocin HDX-2 was classified as a class IIa bacteriocin. FT-IR and CD spectroscopy indicated an excessive proportion of α -helix structures. The MIC of enterocin HDX-2 against Listeria monocytogenes CMCC 1959 was 5.07 ± 0.14 μg/mL, and the MBC was 16.58 ± 1.23 μg/mL. Growth curves and time-kill kinetics showed that enterocin HDX-2 possessed a bactericidal action mode with concomitant cell lysis against pathogens. SEM and TEM analyses showed that enterocin HDX-2 prompted modifications in the morphology and, to a larger extent, in the intracellular activities of L. monocytogenes CMCC 1959 cells. Treatment of L. monocytogenes CMCC 1959 cells with enterocin HDX-2 resulted in the leakage of K + and inorganic phosphate, the generation of ATP and UV-absorbing materials, and decreases in ΔΨ and ΔpH. Highlights: Enterococcus faecium HDX-2 could produce a novel enterocin. Enterocin was classified as a class IIa bacteriocin with a high proportion of α -helix structures. Enterocin could inhibit foodborne spoilage and pathogenic bacteria. Enterocin led to the leakage of K + and inorganic phosphate. Enterocin could damage the cell membrane and cause subsequent cell lysis.